Development of Drug Plan and Control App Using ABC, VEN, and Combined Methods for Inventory Control - Tandah, Muhamad Rinaldhi; Ambianti, Nurul; Putri, Yenita Kartika; Diana, Khusnul (Journal of Health and Nutrition Research, 2025)
Drug Plan and Control (Drug PC) application is a web-based digital tool designed to support pharmaceutical management in healthcare facilities by assisting in the planning, monitoring, and control of drug inventories.  This study aimed to enhance the Drug PC (Plan and Control) application by integrating a drug categorization feature to improve pharmaceutical inventory control. Efficient inventory management is critical in healthcare, as poor control can lead to shortages, overstocking, and financial inefficiencies. The application was developed using PHP as the programming language and MySQL as the database management system. Drug categorization was performed using the ABC method, the VEN method, and a combination of both (ABC-VEN matrix). To evaluate the application's performance, Blackbox testing was conducted to assess the functionality of the user interface. In addition, manual calculations using Microsoft Excel were performed to validate and compare the application results with drug inventory data from two hospitals. Ethical approval was obtained from the Health Research Ethics Committee of the Faculty of Medicine, Tadulako University. The results demonstrated successful integration and 100% functionality accuracy of the new features. Categorization outputs aligned fully with manual data. Hospital 1 followed a typical ABC distribution (70:20:10%), while Hospital 2 showed deviations. VEN classification revealed a significantly higher proportion of Vital (V) drugs in Hospital 1 compared to Hospital 2 (p < 0.05). Combined ABC-VEN results showed CE (C + Essential) as the most common group. High-cost drugs (Category I) represented the majority of investment in both hospitals. In conclusion, the study shows that integrating categorization methods into digital tools like Drug PC can enhance drug inventory control, improve procurement planning, and optimize healthcare resource allocation.